Role of JNK signaling in oral cancer: A mini review - Ioannis Gkouveris; Nikolaos G Nikitakis (Tumor Biology)
JNKs (c-Jun N-terminal kinases) belong to mitogen-activated protein kinases’ family and become activated by several growth factors, stress, radiation, and other extracellular signals. In turn, JNK activation results in phosphorylation of downstream molecules involved in many normal cellular processes. Nevertheless, recent data have linked JNK signaling with several pathological conditions, including neurodegenerative diseases, inflammation, and cancer. The role of JNK in cancer remains controversial. Initially, JNK was thought to play a rather oncosuppressive role by mediating apoptosis in response to stress stimuli, inflammatory, or oncogenic signals. However, a number of studies have implicated JNK in malignant transformation and tumor growth. The contradictory functions of JNK in cancer may be due to the diversity of JNK upstream and downstream signaling and are under intensive investigation. This review summarizes current literature focusing on the significance of JNK pathway in cancer development and progression, particularly addressing its role in oral cancer. Understanding the complexity of JNK signaling has the potential to elucidate important molecular aspects of oral cancer, possibly leading to development of novel and individualized therapeutic strategies.